(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Ecological education is an educational process aimed at forming a person’s attitude to the environment, protecting nature and developing ecological consciousness. The psychological characteristics of this process include a person’s attitude to the ecological environment, his emotional and mental development, as well as his views on environmental issues in the social and cultural context.